Social transformation paradigm: paradoxes between traditionalism and modernism in Pakistan and India - Turar, A. (Journal of Oriental Studies, 2022)
The social transformation is the process of planned changes at large scale in a given society. In other words a shift in the social consciousness at individual, collective, regional and global levels is considered social transformation through which new dimensions come ahead and help in resolving social problems. The social transformation in Indian and Pakistani society reflects a conflict between traditionalism and the modernism. The social alteration in the value system a divergence seems to have been developed between the social groups that has generated a conflict between the modern issues of self-existence and traditional values. For this paper makes consideration of the main traits of social alteration that create the conflict among the traditionalists and the modernists in India and Pakistan. Furthermore, the impact of the highly developed countries of the world, the role of mass media of communication, migration, cultural diffusion, the literacy and finally the socio-political awareness among the people to help develop secularism are considered key tools to look towards modernity that is challenging the traditional paradigms of society. This relationship forms the dialectics of traditionalism and modernity and in that sense what is paradox is that traditionalism and modernity are not mutually restricted but complementary to each other and demonstrate through elements of social changes. The process of modernization in India and Pakistan is proceeding by inventing new traditions, which is combined with economic status, caste system, ethnicity, subcultures. It also emphasizes on the impact of the transformation in the different sections of Indian and Pakistani society and level of social stability through the time. Our objective in the present article is to examine social change in India and Pakistan with the ideological perspective of modernization. Key words: India, Pakistan, society, social transformation, traditionalism, modernism.